Conscious Self-Regulation and Psychological Well-Being as Resources for Academic Success in Young Adolescents: A Structural Model - I.N. Bondarenko; T.G. Fomina (Moscow State University of Psychology and Education, 2023)
The problem of psychological resources of academic achievement is the actual problem of psychology and pedagogy. In the present study on the basis of V.I. Morosanova's resource approach to conscious self-regulation and the results of empirical researches the model of relationship between conscious self-regulation of academic goals achievement, psychological well-being and academic performance in young adolescence was verified. Sample: fifth grade students (N=234, mean age M=11,00, SD=0,28). Research methods: V.I. Morosanova's questionnaire "Self-regulation style of learning activity SSUD-M"; "Scale of manifestations of psychological well-being of adolescents"; "Big Five – child version"; "Attitude to learning in middle and high school". The model of academic success predictors describes the mutual determination of self-regulation, personality (Big Five), achievement motivation, and reveals the direction of cause-effect relationships between variables. It is shown that self-regulation, psychological well-being and achievement motivation are instrumental resources of academic performance. The high own contribution and strengthening of the influence of well-being and motivation on academic achievement provides it key role among its psychological resources. The findings are of practical importance for the organization of psychological support for the education of young adolescents during the transition to the secondary school.